Impact of fintech on microfinance institutions of Peru: efficiency and financial inclusion in 2023 - Chavez Merino, Cedric Vladimir (2025)
Objective: This study had as purpose to analyze the impact of the adoption of financial technologies (fintech) on microfinance institutions in Peru during 2023, evaluating its influence on operational efficiency and financial inclusion, with an emphasis on expanding services in rural areas and traditionally underserved populations. Materials and methods: The research is quantitative, descriptive, and longitudinal, based on secondary data from official sources such as the SBS, the BCRP, and ASOMIF, complemented by information from the World Bank, IMF, and the IDB. Indicators such as creditician portfolio, operating costs, delinquency, and geographic coverage were employed. The analysis was conducted using statistical tools, specifically IBM SPSS version 25, to validate results and ensure accuracy. Results: The findings show an average 45.3% reduction in operating costs per transaction, a 31.7% decrease in the default rate, and a 40.2% increase in the number of clients served. Furthermore, credits granted in rural areas increased by 50.7%, evidencing that the adoption of fintechs optimized internal processes and expanded financial access, particularly in remote regions. Conclusions: The fintechs represent a key tool for improving efficiency and promoting financial inclusion in Peru. However, the magnitude of the benefits depends on each entity's technological capacity and prior investment. It is necessary to strengthen digital infrastructure, training, and implementation strategies to close gaps and consolidate economic development in vulnerable communities.